A pilot facility for analysis and simulation of smart microgrids feeding smart buildings. (May 2016) - Bracco, Stefano; Delfino, Federico; Pampararo, Fabio; Robba, Michela; Rossi, Mansueto
Abstract: In this paper, the economic and environmental assessment of a system composed by a Smart Polygeneration Microgrid (SPM) and a Sustainable Energy Building (SEB) is performed, with specific reference to a pilot facility installed at the Savona Campus and managed by the University of Genoa Power Systems Research Team. The analysis includes the evaluation of operational costs and CO2 emissions, and is carried out in two steps: firstly, the quantification of the economic and environmental benefits provided by the SPM and the SEB on a yearly timescale is determined. Then, the same analysis has been done on a short-term horizon by the use of an optimization algorithm included in the SPM supervisory software. Such a model minimizes an objective function related to daily operational costs and includes the SPM electric and thermal power plants and loads, the distributed heating network, an active building (SEB) and the ICT system responsible for the operational management of the whole research infrastructures. The results of the analysis and the performed experimental research contribute to develop a set of Key Performances Indicators (KPIs) suitable for the smart microgrid concept deployment.